Manufacture of Artificial Heart Valves - Abd , Fatima Naji; Kazem , Taiba Al-Zahraa Naeem; Ali , Aya Sami; Jabbar , Fatima Raouf (American Journal of Botany and Bioengineering, 2024)
The heart is one of the most important organs in the human body. Improper functioning of the heart mainly affects the lifespan of the human being. There are several diseases that affect the heart, and in some conditions, these can result in failures. Diseases that affect the heart include valvular disease, obstructions in the blood vessels, heart muscle diseases, and heart failure. In all these cases, healthy valves will not be able to function properly. There are four valves present in the heart (two atrioventricular valves and two semilunar valves). Valvular disease mainly occurs in aged persons. In valvular disease, the valve will not function properly, causing the backward flow of blood. In all these conditions, it can be replaced by artificial valves. Quality valves can be manufactured using materials like metals and ceramics, where study is difficult to perform. As polymers are more flexible than metals and ceramics, they are suitable for designing numerous types of artificial valves. There are two types of artificial valves: mechanical valves and bio-prosthetic valves. More research has been carried out to make artificial valves using biocompatible polymer materials and to add features like antithrombogenic properties and cell compatibility. Measures should be taken to ensure that, before using artificial valves in clinical treatments, mechanical testing should be performed to check the valve function and wearability. There is no manual work to produce regular artificial heart valves; instead, the valves can be adapted to CAD, CAM, or rapid prototyping techniques. In recent years, the use of 3D printing in heart valves has yielded better results. Biocompatibility criteria should be analyzed based on the fabrication methods. Cartilage formation in existing artificial valves is known to decrease with the number of hinge paddles, larger valves, and small computational pressure.